Analisis Kandungan Vitamin C pada Buah Naga yang Diperjualbelikan Di Sekitar Kota Makassar - Husnita Yahya (Jurnal Media Laboran, 2017)
This research background of dragon fruit belonging to the fruit of great benefits and is a nutritious enough food for human health. One of them is vitamin C content that is useful to boost immunity, lower cholesterol, increase appetite, launch defecate, strengthen bones and teeth also for slippery, smoothness of skin and prevent acne. This research was conducted at Central Health Laboratory of Makassar on 29 - 4, April - May 2016. The purpose of this research is to find out how much vitamin C content in dragon fruit. From dragon fruit research taken randomly from five different traders around Makassar city, it is known 100% contain vitamin C which is high enough with acquisition value 128,24-166,48 ug / g